The effect of lavender essential oil aromatherapy on sleep quality in hemodialysis patients - Niken Setyaningrum; Aris Setyawan; Difran Nobel Bistara (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2022)
Hemodialysis is a long-term therapy that must be undertaken by patients with chronic kidney disease. Patients who undergoing therapy for a very long time will have an impact on the patient's psychology. One of the psychological effects that arise is a sleep disorder. Poor sleep quality can lead to physiological changes, the endocrine system, cardiovascular system, and immune and nervous systems. To overcome sleep disorders in hemodialysis patients, non-pharmacological options can be used, namely Lavender Essential Oil Aromatherapy via inhalation. The purpose of this study was to determine the effect of Lavender Essential Oil Aromatherapy on Sleep Quality in Hemodialysis Patients. The study was conducted on 32 hemodialysis patients, divided into two groups, there are 16 intervention groups and 16 control groups. The intervention was carried out for 3 times of administration during intra-hemodialysis. The instrument used is the Pittsburgh Sleep Quality Index (PSQI) applied pre and post-test. Test data analysis using the independent samples test showed that there was a difference in the average score for sleep quality with a p-value of 0.000, it means that there was an increase in sleep quality in patients undergoing hemodialysis for intervention groups. Lavender Essential Oil Aromatherapy can be applied as an effective nursing intervention to overcome sleep quality disorders in patients undergoing hemodialysis. Abstrak: Hemodialisis merupakan terapi jangka panjang yang harus dilakukan oleh pasien dengan penyakit ginjal kronik. Pasien yang menjalani terapi dalam waktu yang sangat lama akan berdampak pada psikologi pasien. Salah satu dampak psikologis yang muncul adalah gangguan tidur. Kualitas tidur yang buruk dapat menyebabkan perubahan fisiologis, sistem endokrin, sistem kardiovaskular, sistem kekebalan dan saraf. Untuk mengatasi gangguan tidur pada pasien hemodialisa dapat digunakan pilihan nonfarmakologi yaitu Aromaterapi Minyak Atsiri Lavender melalui inhalasi. Tujuan penelitian ini adalah untuk mengetahui pengaruh Aromaterapi Minyak Atsiri Lavender terhadap Kualitas Tidur pada Pasien Hemodialisis. Penelitian dilakukan pada 32 pasien hemodialisa yang terbagi menjadi dua kelompok yaitu 16 kelompok intervensi dan 16 kelompok kontrol. Intervensi dilakukan selama 3 kali pemberian selama intra hemodialisis. Instrumen yang digunakan adalah Pittsburgh Sleep Quality Index (PSQI) yang diterapkan sebelum dan sesudah intervensi. Analisis data uji dengan menggunakan independent sample test menunjukkan bahwa terdapat perbedaan rata-rata skor kualitas tidur dengan nilai p value 0,000 artinya terjadi peningkatan kualitas tidur pada pasien yang menjalani hemodialisis kelompok intervensi. Aromaterapi Minyak Atsiri Lavender dapat diterapkan sebagai intervensi keperawatan yang efektif untuk mengatasi gangguan kualitas tidur pada pasien yang menjalani hemodialisis.